Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sepeda Motor Honda Beat Pada PT Daya Anugrah Mandiri - Anugrah Ilahi, Andi Alfianto; Arfah, Aryati; Arif, Muhammad (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The purpose of this study was to find out how much influence Product, Price, Promotion and Place had on the Purchase Decision of a Honda Beat motorcycle using the SPSS 20 analysis method. The results showed that: 1. Product (X1) did not affect the purchase decision variable (Y) because tcount1.618≤ttable (2.085) and a significant probability of (0.003)≤ α (0.05). 2. Price (X2) does not affect the purchase decision variable (Y) because tcount 0.865 ≤ t table (2.085) and a significant probability of (0.005) ≤ α (0.05). 3. Promotion (X3) has a positive and significant effect on decisions purchase (Y) because tcount5.006≥ttable (2.085) and a significant probability of (0.000)≤ α (0.05). 4.Place (X4) has a positive and significant effect on purchasing decisions (Y) because tcount2.673≥ttable (2.085) and a significant probability of (0.001)≤ α (0.05).5. Product (X1) Price (X2) Promotion (X3) and Place (X4) have a positive (22.845) and significant (0.000 ≤ 0.05) effect on the Purchase Decision variable (Y) at PT. Daya Anugrah Mandiri Parepare Branch.